Proton transfer pathways in an aspartate-water cluster sampled by a network of discrete states - Reidelbach, Marco; Betz, Fridtjof; Maeusle, Raquel Maya; Imhof, Petra (Chemical Physics Letters, 2016)
Proton transfer reactions are complex transitions due to the size and flexibility of the hydrogen-bonded networks along which the protons may “hop”. The combination of molecular dynamics based sampling of water positions and orientations with direct sampling of proton positions is an efficient way to capture the interplay of these degrees of freedom in a transition network. The energetically most favourable pathway in the proton transfer network computed for an aspartate-water cluster shows the pre-orientation of water molecules and aspartate side chains to be a pre-requisite for the subsequent concerted proton transfer to the product state.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Discretisation; Proton transfer; Reaction pathways; Sampling; Transition network